PENGEMBANGAN WEBSITE DSS DI PT XYZ UNTUK BANTUAN PENDANAAN UMKM KOTA MATARAM MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Safa Salsabila Damara; Darwiyanto, Eko; Gandhi, Arfive (Indonesia Journal on Computing (Indo-JC), 2024)
This research aims to design and develop an efficient funding website for Micro, Small,and Medium Enterprises (MSMEs) in Mataram City using the Simple Additive Weighting(SAW) method at PT XYZ. The background of the research is based on challenges suchas the manual selection of MSMEs, which can be time-consuming and prone to errors incalculating scores or values. Additionally, the criteria scores lack a definite average valuefor each category, and there is a risk of losing MSME application documents due todisorganized collection, leading to scattered documents. In this advanced era, manycompanies use websites to support their programs, while PT XYZ still lacks such aplatform to support its funding program. Given these challenges, a website is needed tosupport the funding program and address existing issues. This research uses a qualitativeapproach, collecting data through literature studies, interviews, and observations. Theresults of this research show that using the Simple Additive Weighting (SAW) methodyields consistent final values in both manual and program-based tests and enables fasterselection